PERTUMBUHAN DAN SURVIVAL RATE IKAN NILA (Oreochromis. Sp) STRAIN MERAH DAN STRAIN HITAM YANG DIPELIHARA PADA MEDIA BERSALINITAS - M. Yusuf Arifin (Universitas Batanghari Jambi, 2016)
This research aims to test the growth and survival of fish tilapia (Oreochromis. SP) strains of red and black strains maintained at Tanjung Jabung Regency in the embankment of the Western media in salinity of the water. The results of this research diharapan one of the strains of Tilapia fish can serve as an alternate replacement for the cultivation of shrimp that are considered not suitable to be kept on a farm in the area.This research was conducted in September through December 2015 which is located in the village of Tanjung Jabung Regency Dualap River West of Jambi. The fish test fish tilapia strains used are red and black strains obtained from Freshwater Cultivation Hall (BBAT) Jambi with a weighted average of 8 grams/tail.The parameters observed is the growth rate and survival rate. The data obtained were analyzed statistically using t-Test. Maintenance of test fish was performed for 60 days with a time of sampling that is day 0, 30, 60, and 90 day.Keyword : growth, media in salinity